Clozapine vs. Haloperidol in Aggression Prevention - Steven Hunt; Robyn Gorham; Elena Hunt (European Scientific Journal, ESJ, 2019)
Nurses and physicians working in forensic psychiatric facilities are frequently exposed to violent incidents at the hands of forensic psychiatric patients and inmates. Aside from seclusion, segregation and restraint, prevention serves as an efficient strategy in dealing with violence and aggression, including a proper medication regimen. This paper aims to address a specific clinical research question in terms of prevention of violence and aggression among forensic psychiatric patients, from a pharmaceutical perspective. Clinical Question: In forensic psychiatric patients with a history of aggression, is regular use of Clozapine more effective in reducing the incidence of violence and/or aggression than regular use of Haloperidol? Five primary research studies were found to be specific to the clinical question and its context. Review results: Resulting from its superior efficacy in treating complicated, positive schizophrenia symptoms, including violence and aggression, Clozapine may be better situated to prevent aggressive incidents among Forensic Patients with a history of aggression. Answering the clinical question has led to reflection and application of new recommendations of pharmaceutical interventions in a forensic setting.